2020
DOI: 10.1177/1059601120910859
|View full text |Cite
|
Sign up to set email alerts
|

“One Size Does Not Fit All”: Revisiting Team Feedback Theories From a Cultural Dimensions Perspective

Abstract: Feedback is a critical component of teamwork regulation. Research underscores the importance of feedback processes for its effectiveness in teams and further notes how individual differences can affect these processes. Nonetheless, few have theorized on the cultural dimensions associated with feedback to specify how these can attenuate such processes. We contend that research can be advanced by specifying how cultural dimensions may shape individual perception and processing of feedback and team processing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 191 publications
(234 reference statements)
0
7
0
1
Order By: Relevance
“…This supports past research showing that team composition— related to personality in these studies—may be a relevant factor for inculcating team norms (Gonzalez-Mulé et al, 2014; Raver et al, 2012). Gabelica and Popov (2020) noted advances made in recent research to expand the number of criterion variables examined with regard to cultural value effects. Our study contributes to this positive trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…This supports past research showing that team composition— related to personality in these studies—may be a relevant factor for inculcating team norms (Gonzalez-Mulé et al, 2014; Raver et al, 2012). Gabelica and Popov (2020) noted advances made in recent research to expand the number of criterion variables examined with regard to cultural value effects. Our study contributes to this positive trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been widely studied that culturally heterogeneous teams can achieve higher levels of innovativeness and performance than culturally homogeneous teams ( Feitosa et al, 2018 ; Stahl and Maznevski, 2021 ). Teams with members from various cultures can provide a broader range of perspectives, task-related knowledge, abilities, and skills ( Gabelica and Popov, 2020 ).…”
Section: Cultural Diversity and Multicultural Team Performancementioning
confidence: 99%
“…Supporting this research, a previous study conducted by Josephine and Riantoputra [25] in Indonesia showed a high correlation between MMBTP and MMBIF, while Mero et al's [17] study conducted in America showed an insignificant correlation. Cultural factors might explain the difference in the correlation between MMBTP and MMBIF in Indonesia and America, as cultural factors can influence how individuals perceive and process feedback, such as in the process of mentoring [60]. Further research may want to investigate cultural factor, such as high power distance, that potentially affect the way employees perceive monitoring behavior from their leaders.…”
Section: Plos Onementioning
confidence: 99%